Optimalisasi Pengelolaan Data Guru Bahasa Inggris dengan Sistem Informasi Berbasis Teknologi MA Al-Falah Palembang : - Sari, Novita; Iryanti, Nurlista; Fitri, Hidayatul; Hakim, Arif Rahman; Aulia, Nyimas (Journal of Social and Community Service, 2024)
Teacher data management is one of the important aspects in improving the efficiency and quality of educational administration. However, many educational institutions, including Madrasah Aliyah (MA) Al-Falah Palembang, still face obstacles in managing teacher data that is less structured and manual. This can hinder access to information, data accuracy, and data-based decision making. This community service activity aims to optimize the management of English teacher data at MA Al-Falah Palembang through the implementation of a technology-based information system. This information system is designed to facilitate the process of recording, searching, updating, and reporting teacher data efficiently. The methods used include needs analysis, system development, system usage training for teachers and administrative staff, and implementation evaluation. The results of this activity are expected to improve the efficiency of teacher data management, minimize errors in data processing, and support better decision making in the MA Al-Falah Palembang environment. In addition, the implementation of this system is expected to be a model that can be applied in other educational institutions to improve the quality of educational data management.